The Influence of the Traditional Lemon Nipis Game on Children's Cognitive and Social-emotional Development at Paud Mawar FKIP Unpati Ambon - Lokollo, Lamberthus. J.; Noya, Ferdinanda S. (KnE Social Sciences, 2024)
This study aimed to find out the impact of traditional game “Lemon Nipis” toward the development of the cognitive and social emotions of children at PAUD Mawar FKIP Unpati Ambon. The type of this study used was experiment. The participants of this study were 12 children. The instrument are applied as instrument research are observation and documentation. Based on the result of this study, it shows that the ability of cognitive and social emotion of children at PAUD Mawar Unpatty, Ambon before the study obtained an average pre-test score of 15.46, while the post-test average score was 46.31. While, the results of t test is the significance value (2-tailed) 0.000 < 0.05. If the significant value is < 0.05 it means that Ho is rejected and Ha is accepted. Based on the t test results, it shows that the traditional game “Lemon Nipis” have an impact toward the development of the cognitive and social emotion of children at PAUD Mawar FKIP Unpati. Keywords: traditional game, children cognitive, social emotional development